Teacher training and education in the presence of the new framework of learning and teaching through competences - CANO GONZÁLEZ, RUFINO (Paideia Revista de Educación, 2020)
The new profile of teaching professionals and, consequently, teacher training and education in the presence of the present framework of learning and teaching through competences, can be understood by reconsidering and transforming the special requirements that the practice of the teaching profession demands. This involves a profound change from the point of view of the shape and design of the incipient models of training and education of future teachers founded on independent work, lifelong learning processes and a dimension which is essentially Learningorientation and tutoring, which must illuminate the professional action of teachers.